2015
DOI: 10.1016/j.jmmm.2015.05.093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the double-counting functional on the electronic and magnetic properties of half-metallic magnets using the GGA+U method

Abstract: Methods based on the combination of the usual density functional theory (DFT) codes with the Hubbard models are widely used to investigate the properties of strongly correlated materials. Using first-principle calculations we study the electronic and magnetic properties of 20 halfmetallic magnets performing self-consistent GGA+U calculations using both the atomic-limit (AL) and around-mean-field (AMF) functionals for the double counting term, used to subtract the correlation part from the DFT total energy, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
(84 reference statements)
4
11
0
Order By: Relevance
“…59 and implemented in the FP-LAPW package Elk 60 . It was found that both Co 2 MnSi and Co 2 FeSi are better described with the AMF scheme, as indicated by their small α U parameter of ∼ 0.1 for both materials (α U = 0 denotes complete AMF and α U = 1 FLL), which is in agreement with the recent work by Tsirogiannis and Galanakis 61 . To test whether a more sophisticated way to treat correlation effects improves the description of these materials, electronic structure calculations for Co 2 MnSi and Co 2 FeSi using the DMFT scheme were performed.…”
Section: Electronic Structuresupporting
confidence: 89%
“…59 and implemented in the FP-LAPW package Elk 60 . It was found that both Co 2 MnSi and Co 2 FeSi are better described with the AMF scheme, as indicated by their small α U parameter of ∼ 0.1 for both materials (α U = 0 denotes complete AMF and α U = 1 FLL), which is in agreement with the recent work by Tsirogiannis and Galanakis 61 . To test whether a more sophisticated way to treat correlation effects improves the description of these materials, electronic structure calculations for Co 2 MnSi and Co 2 FeSi using the DMFT scheme were performed.…”
Section: Electronic Structuresupporting
confidence: 89%
“…Due to the existence of the energy gaps in the electronic band structure one could envisage using also approximations beyond the standard functionals like (a) the orbital dependent functionals [34], (ii) the Hubbard LDA + U schemes [35,36], or (iii) hybrid functionals like the Heyd-Scuseria-Ernzerhof functional [37,38]. Such schemes are known to alter in several cases the results obtained with the standard LDA or GGA schemes, and sometimes they also produce contradictory results.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the GW approach corrects the band gaps from their (usually underestimated) DFT values towards experiment. Furthermore, it is known to produce more accurate results for halfmetallic Heusler compounds than other simplified approaches such as GGA+U [60,61]. For the half-metallic Heusler compounds Co 2 MnSi and Co 2 FeSi, it has also been shown to be able to accurately reproduce the experimental photoemission and x-ray absorption spectra [62].…”
Section: ∆Ementioning
confidence: 99%